Psoriatic arthritis (literature review) - N. S. Asfandiyarova; R. R. Shilin (Klinicist, 2024)
Psoriatic arthritis (PsA) is a chronic immune-inflammatory progressive disease of the musculoskeletal system observed in psoriasis, which affects the joints, spine and entheses; it occurs in the form of arthritis, dactylitis, enthesitis, and can also manifest as spondylitis or sacroiliitis. The etiology of PsA is unknown, but the pathogenesis has been studied in more detail. Under the influence of external factors, such as infectious agents (viruses, bacteria, fungi), neuropsychic stress, injuries, drugs, changes in intestinal microbiota, etc., genetically predisposed individuals experience activation of the immune system, both congenital and acquired. Currently, there are 5 clinical forms of PsA: predominantly lesion of the distal interphalangeal joints of the hands and feet, distal form; mutilating arthritis; psoriatic spondylitis; asymmetric mono-oligoarthritis; symmetrical polyarthritis, rheumatoid-like form. Along with the characteristic symptomsof skin and joint damage, patients with PsA note a decrease in the quality of life, general malaise, fever, enlarged lymph Review nodes, weight loss, signs of comorbid pathology (obesity, diabetes, cardiovascular diseases). Arthritis is accompanied by tendinitis, synovitis, enthesitis. Isolated spinal damage (psoriatic spondylitis) is rare, it is usually combined with peripheral arthritis, characterized by pain in the spine, dysfunction, curvature. Differential diagnostics are carried out with rheumatoid arthritis, gout, ankylosing spondylitis, polyosteoarthritis, infectious forms of joint damage, joint damage in chronic inflammatory bowel diseases. Treatment of PsA should include medication, physiotherapy and spa treatment. Usually, treatment of PsA begins with the use of such drugs as methotrexate, leflunomide, sulfasalazine, cyclosporine A; non-steroidal anti-inflammatory drugs and intra-articular administration of glucocorticosteroids are used as an auxiliary agent, they are classified as symptom-modifying drugs, they partially improve the patient’s quality of life, reduce pain, but have little effect on the progression of the pathological process. In the absence of an effect from previously conducted treatment and contraindications, genetically engineered biological drugs are used.